Chimeric antigen receptor T cell immunotherapy for multiple myeloma: A review of current data and potential clinical applications. (25th February 2019) - Susanibar Adaniya, Sandra P.; Cohen, Adam D.; Garfall, Alfred L.
Abstract : Multiple myeloma (MM) is a malignant plasma cell disorder that remains incurable for most patients despite significant improvements achieved with modern therapy. Tumor evasion is a key process in the pathogenesis of MM and a compromised immune system is associated with more aggressive forms of the disease. In contrast, the emergence of myeloma‐specific immune responses after both autologous and allogeneic stem cell transplantation is associated with better prognosis. Adoptive T cell therapies may improve specific anti‐myeloma immunity resulting in long‐lasting remissions. CAR T cell therapies for MM are at an early stage of clinical development. To date, anti‐BCMA CAR T cells have shown the greatest results in early‐phase clinical trials. Toxicities have included cytokine release syndrome (CRS) and neurotoxicity. Current areas of research in CAR T cell therapies include the use of gene‐editing to enhance their effectiveness and safety, the integration of CAR T cells with other therapies (immunomodulatory drugs, checkpoint inhibitors) and CAR T cells to target multiple antigens.